Corporate Governance Mechanism, Ownership Structure, and Firm Performance : Evidence from India - Jain, Surbhi; Kaur Dhillon, Lakhwinder; Aggarwal, Rashmi; Bagga, Teena (Indian Journal of Finance, 2023)
Purpose : Corporate governance (CG) is the mechanism to direct and control companies. Corporate governance and ownership structure have a direct influence on firm performance. This research paper examined the relationship among three variables: CG, ownership structure, and firm performance. Methodology : CG mechanisms included board independence, CEO duality, and audit committee independence. Insider ownership and foreign ownership determined ownership structure. Return on assets and return on equity were used to assess a company’s performance, and Tobin’s Q was used to assess market performance. A sample of 50 NSE-listed firms was taken. STATA 14.1 was used for analysis, and multiple and hierarchical regression were used. Findings : The findings indicated that CG variables and ownership structure positively affected firm performance. To elaborate, CEO duality, audit committee independence, insider ownership, and foreign ownership were positively related to firm performance. However, board independence was the only variable that influenced firm performance negatively. Practical Implications : One of the studyâ€™s essential findings was the negative impact of board independence on firm performance. This had some practical implications because only a few persons are qualified to act as independent directors. Hence, one person is appointed in many companies simultaneously, leading to biased decision-making. Thus, companies must ensure that independent directors are appointed after proper screening and deliver their duties as expected. Originality : Instead of utilizing the standard system found in the literature, we relied on a single measure structure and used a variety of CG mechanisms.